Hutang Uang Dibayar Emas dan Akibat Hukumnya Terhadap Para Pihak - Mahyuni, Mahyuni; Zulhamdi, Zulhamdi; Ulfah, Almira Keumala (el hisbah Journal of Islamic Economic Law, 2024)
This study aims to analyze the payment of debt with gold and its legal consequences for the parties. The research method uses empirical juridical with a qualitative approach. This study was conducted in the Muslim community in North Aceh Regency. Data collection techniques use observation, interviews and documentation. The analysis technique uses an interactive model. The research findings were analyzed using the perspective of Islamic economic law. The results of the study indicate that the mechanism for paying debts with gold in North Aceh Regency, initially the debtor (muqtarid) receives money from the price/measurement of gold then returns it to the creditor (muqrid) with previously measured gold. Reviewed from Islamic economic law, paying debts with gold in North Aceh Regency violates the pillars of debt and receivables. In debt and receivable transactions, "it is obligatory for the borrower to return the missile of the property that is owed to him". As a solution, hillah (حيلة) is carried out, namely money is turned into gold and then paid with gold, this is formally valid but not morally valid because it is contrary to the principle of mutual assistance in Islamic economic law. This study contributes to the development of Islamic economic law, especially as a reference for debt and receivables transactions as prescribed by Islam.